2000
DOI: 10.1002/(sici)1521-1878(200001)22:1<32::aid-bies7>3.3.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

The clocks controlling the tide-associated rhythms of intertidal animals

Abstract: The living clock that governs tide-associated organismic rhythms has previously been assumed to have a fundamental period of approximately 12.4 h, an interval that reflects the average period of the ebb and flow of the tide. But, in 1986, marine chronobiologists began to accumulate laboratory results that could not be explained by the action of such a clock. Prime among these findings was the discovery that, occasionally, one of the two daily peaks in an organism's rhythm assumed a different period from its pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 0 publications
0
40
0
Order By: Relevance
“…Palmer 2000). Many investigators have suggested sperm limitation as an ultimate cause for species with external fertilization (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Palmer 2000). Many investigators have suggested sperm limitation as an ultimate cause for species with external fertilization (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The 2 low tides each day may each entrain an endogenous clock of an intertidal organism, i.e. there are 2 tide-entrained endogenous clocks (see Palmer 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In invertebrates, weakness in the detected circadian regulation is due to the splitting of activity peaks into submultiple units when animals are transferred to the laboratory (e.g. Dowse and Palmer, 1990;Warman and Naylor, 1995;Palmer, 2000;. The animals showed a measurable fan activity rhythm in both photoperiod treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Bünning & Müller 1962, Christy 1978, Saigusa & Hidaka 1978, Neumann 1981, Palmer 2000, Hsueh 2002, Lüning et al 2008, Oliveira et al 2009). For example, the reproductive activities of many marine species, such as corals (Harrison et al 1984), echinoderms (Kubota 2000, Morgan 2009), crustaceans (Morgan 1996), or fishes (Hsiao & Meier 1986, Susilo et al 2009) all exhibit lunar or semilunar cycles.…”
Section: Introductionmentioning
confidence: 99%